Entrepreneurial Marketing Skills and Growth of Small and Medium Plastics Manufacturing Enterprises in Nigeria - Dauda, Jolly; Namusonge, Gregory; Nyang'au, Samson (International Journal of Entrepreneurship and Project Management, 2023)
Purpose: The purpose of this study was to determine the influence of entrepreneurial marketing skills on growth of small and medium plastic manufacturing enterprises in Nigeria. Methodology: Descriptive research design was applied by the study. The study target population was 18,476 plastics manufacturing SMEs in LAGOS State, Nigeria. Based on Yamane Formula adopted the sample size for this study was 397 respondents. Random sampling was used to select the 392 plastics manufacturing SMEs. The study therefore randomly selected 392 plastics manufacturing SMEs from a list of total lists of these is 18476 plastics manufacturing SMEs in LAGOS State, Nigeria. The study used semi structured questionnaires to collect primary data. The study used SPSS version 27 software to analyse the data. Both descriptive and inferential analyses were carried out. Results from analysed data were presented in tables and figures. Results: The inferential statistics results revealed a positive and significant relationship between entrepreneurial marketing skills on growth of small and medium plastic manufacturing enterprises in Nigeria at p<0.05. Entrepreneurial marketing g skills on growth of small and medium plastic manufacturing enterprises had a Pearson's correlation of r=0.808 (p=0.000). The correlation results implied that implied that entrepreneurial marketing skills had very strong positive correlation with growth of small and medium plastic manufacturing enterprises in Nigeria. The finding implied that improving the marketing skills for SMEs entrepreneurs would results to high growth of heir enterprises. The R2 for the model was 0.653 indicating that 65.3% of growth of SMEs is explained by entrepreneurial marketing skills other factors held constant. This was a sign that the model was appropriate for establishing the relationship between entrepreneurial marketing skills on growth of small and medium plastic manufacturing enterprises in Nigeria. Unique Contribution to Theory, Practice and Policy: Life Cycle Theory used in this study may be used to anchor future studies on describing the different stages of corporate life. The study recommends that SMEs owners should invest in capabilities that will enable gather market information in the industry they operate. This will ensure that marketing approach and their entire growth model is streamlined to optimize market segment that have the largest potential for growth. According to the study, policy makers should formulate policies that will ensure that SMEs are trained on entrepreneurial marketing skills and financial management to equip them with adequate skills need to grow their businesses.